Budaya Kejujuran dalam Menghadapi Perubahan Zaman (Studi Fenomenologi Masyarakat Islam Modern) - Muhasim Muhasim (PALAPA, 2017)
The change of phenomenon is eternally and the change of epoch like a turn of seasons at the certain period of time, such as the change of days, months, years and centuries. Nowadays, we life in 21st century or globalization era. It is indicated by the dramatic change. And it is also as the result of advance in science, digital revolution and the progress of transportation. This condition makes the world seems like to be so narrow, the turn of time feels so fast, the distance become closer. As the fact , today the long distance we can reach within hours and the information can be received very fast. This era’s transformation has effect for somebody or society in his act and attitude. Such as the honesty damaging because of an importance, and somebody may act and pretend based on the condition. So that why, the focus of this discourse is to investigate the practice of honesty in globalization era. The method used in this research is descriptive method. In where, the understanding based on the object, the analyzing of various situation and social reality in society based on and the truth sources and some articles from online media which related with the object of this research. Hopefully, by this method can help to investigate, and analyze the honesty practice in the globalization era. Honesty has a moral value. It has influence to form a strong mentality in rising the competence and the hard worker, to face the globalization challenging in all job sectors. At the end, the honesty not only about the attitude, but also the dignity. The dignity and identity personally and nationally.